Performing advanced analytics on relational data with Spark SQL - Armbrust, Michael (O'Reilly Media, 2014)
"In this event, we'll examine Spark SQL, a new Alpha component that is part of the Apache Spark 1.0 release. Spark SQL lets developers natively query data stored in both existing RDDs and external sources such as Apache Hive. A key feature of Spark SQL is the ability to blur the lines between relational tables and RDDs, making it easy for developers to intermix SQL commands that query external data with complex analytics. In addition to Spark SQL, we'll explore the Catalyst optimizer framework, which allows Spark SQL to automatically rewrite query plans to execute more efficiently."--Resource description page.